Nutritional Status and Dietary Patterns as Determinants of Infertility Among Reproductive-Age Couples: A Cross-Sectional Analysis - Erna Yovi Kurniawati; Lia Dian Ayuningrum (Jurnal Riset Daerah, 2026)
Infertility is a multifactorial reproductive health issue that affects a growing number of couples globally. Nutritional status and dietary patterns have been increasingly recognized as modifiable factors influencing fertility, yet their impact remains underexplored in many low-resource settings, including Indonesia. This study aimed to assess the association between nutritional status and dietary patterns with infertility among reproductive-aged couples in Bantul, Yogyakarta. A cross-sectional analytical study was conducted involving 204 participants (102 infertile and 102 fertile couples) selected using stratified random sampling. Nutritional status was determined based on body mass index (BMI), while dietary patterns were assessed using a validated food frequency questionnaire. Statistical analyses included chi-square tests and multivariate logistic regression to evaluate associations and calculate adjusted odds ratios (ORs) with 95% confidence intervals (CIs). The findings indicate that underweight and overweight/obese individuals had significantly higher odds of infertility compared to those with normal BMI (OR = 2.00 and 1.98, respectively; p < 0.05). Participants with inadequate dietary patterns were 3.29 times more likely to experience infertility (p < 0.001). Multivariate analysis confirmed both nutritional status and dietary patterns as independent predictors of infertility. Nutritional imbalance and poor dietary habits are strongly associated with infertility. These findings underscore the need to integrate nutritional assessment and counseling into fertility care to improve reproductive outcomes. Further interventional studies are recommended to establish causal relationships and guide clinical practice.